Howard and Christine Watkins Rafting Down the Tuolumne River with Echo Company - Watkins, Howard::::::::: (1985)
Howard Watkins, boatwoman, and another woman rider on boat; other boats behind on river Howard with full black beard and wearing blue, white and gold hat